Update on Outcomes of Animal Recording Decision Support System AICCRA – CBBP Integration - Santos, Bruno; van Tonder, Jolene; Teviotdale, Mark; Getachew, Tesfaye; Rischkowsky, Barbara A.; Haile, Aynalem (Accelerating Impacts of CGIAR Climate Research for Africa, 2024)
This report provides a comprehensive update on the outcomes of the animal recording and decision support system Dtreo (Dtreo platform), focusing on the integration of the Community-Based Breeding Program (CBBP) with the Accelerating Impacts of CGIAR Climate Research for Africa (AICCRA) project. This initiative aims to enhance livestock productivity and sustainability through improved data recording and decision-making tools.